Non-contact physical health monitoring in mental health seclusion. (1st April 2022) - Clark, Hannah; Edwards, Allison; Davies, Rebecca; Bolade, Adenike; Leaton, Rachael; Rathouse, Robert; Easterling, Marisa; Adeduro, Ronnie; Green, Matthew; Kapfunde, Wellington; Olawoyin, Oladapo; Vallianatou, Kalliopi; et al.
Background:Patientsin mental health services' seclusion require regular physical health assessments to identify, prevent and manage clinical deterioration. Sometimes it may be unsafe or counter-therapeutic for clinical staff to enter the seclusion room, making it challenging to meet local seclusion standards for physical assessments. Alternatives to standard clinical assessment models are required in such circumstances to assure high quality and safe care. Aim:The primary aim was to improve the quality of physical health monitoring by making accurate vital sign measurements more frequently available. Secondary aims were to explore the clinical experience of integrating a technological innovation with routine clinical care. Method:A non-contact monitoring device was installed in the mental health seclusion room and was used in addition to existing clinical care. Over six months, adherence to local clinical guidelines was compared against a time- period prior to installation. Feedback was sought from staff and patients through questionnaires and focus groups. A quality improvement framework was used to continually improve the process using plan, do, study, act (PDSA) cycles. Results : The non-contact monitoring device enabled a 12.3-fold increase overall in the monitoring of physical health observations when compared to a real-world baseline rate of checks. Enhancement to standard clinical care varied according to patient movement levels. Patients, carers and staff expressed positive views towards the integration of the technological intervention.Conclusion:The non-contact monitoring device improved the quality and safety of care by increasing availability of physical health monitoring. It was positively received by patients, carers and staff.